Mixture Composition Analysis Of Reclaimed Asphalt Pavement (RAP) As Asphalt Concrete – Wiring Course (AC-WC) Layer Against Marshall Characteristic - Wahyu Aunur Rahman Hakim (Journal of World Conference (JWC), 2020)
Reclaimed Asphalt Pavement of national roads in East Java Province can be used at AC-WC, AC-BC, AC-Base layers, with a percentage of RAP usage of 20-40%, optimum RAP of 20-30%, asphalt’s content in RAP of 3,78-4.63% (Widayanti, 2018). The composition of the addition for 20% RAP which is originated by Taman-Waru with natural aggregates produces Marshall stability of 830.482 kg and melting / flow of 3.8 mm (Handayani, 2007). Therefore, it is necessary to have research of the analysis about the composition of the Reclaimed Asphalt Pavement (RAP) in the amount of 25%, 30%, 35% as the Asphalt Concrete - Wiring Course (AC-WC) layer against the characteristics of the Marshall. The purpose of this research are 1.) To find out the optimum asphalt content (KAO) in a mixture of AC-WC (Asphalt Concrete - Wearing Course) asphalt and 60/70 Asphalt mixture with the usage of RAP material and natural aggregate in accordance with the General Specifications of Bina Marga 2018 2.) Knowing the effect of the usage of RAP material and natural aggregate for the gradation of asphalt mixture of AC-WC (Asphalt Concrete - Wearing Course) in accordance with the General Specifications of Bina Marga 2018 3.) Knowing the performance of AC-WC asphalt concrete mixture (Asphalt Concrete - Wearing Course) and 60/70 asphalt mixture of RAP material and natural aggregate in terms of Stability and Marshall Quotient values. The research was carried out by the experimental method through laboratory testing. The expected benefit of this research is the discovery for optimizing of the usage recycle materials from road pavement that will be reused during the implementation of road maintenance work and give an alternative of the minimum natural aggregate’s usage. The result of the testing in the laboratory, the mixture of heat asphalt AC-WC with 25% of RAP, had the highest Marshall stability of characteristic for 1309 kg. It’s caused the new materials of the mixture composition has better quality than the mixture of RAP materials, but the additions of RAP composition for 25%, 30%, 35% still can be used as the alternative substitution of nature aggregate, because those are still the Bina Marga’s specification in 2018 of AC-WC mixture.